Engineering Components of the Lactobacillus S-Layer for Biotherapeutic Applications - Klotz, Courtney; Barrangou, Rodolphe (Frontiers in Microbiology, 2018)
Lactic acid bacteria (LAB) are frequently harnessed for the delivery of biomolecules to mucosal tissues. Several species of Lactobacillus are commonly employed for this task, of which a subset are known to possess surface-layers (S-layers). The S-layer is a two-dimensional crystalline array of repeating proteinaceous subunits that forms the outermost coating of many prokaryotic cell envelopes. Its periodicity and abundance have made it a target for numerous biotechnological applications, including delivery of therapeutic proteins and vaccine antigens. In the following review, we examine the multi-faceted S-layer protein (Slp), and its use in both heterologous protein expression and mucosal vaccine delivery, through its diverse genetic components: the strong native promoter, capable of synthesizing as many as 500 Slp subunits per second; the signal peptide that stimulates robust secretion of target proteins; and the structural domains, which can be harnessed for both cell surface display of a foreign peptide or adhesion enhancement of a host bacterium. Although numerous studies have established vaccine platforms based on one or more components of the Lactobacillus S-layer, this area of research remains largely in its infancy, thus this review not only highlights past works, but also advocates for the future use of Slps in mucosal vaccine research.